Simple, rapid and sensitive detection of Orientia tsutsugamushi by loop-isothermal DNA amplification. - Paris, D; Blacksell, S; Newton, P; Day, N (2008)
We present a loop-mediated isothermal PCR assay (LAMP) targeting the groEL gene, which encodes the 60kDa heat shock protein of Orientia tsutsugamushi. Evaluation included testing of 63 samples of contemporary in vitro isolates, buffy coats and whole blood samples from patients with fever. Detection limits for LAMP were assessed by serial dilutions and quantitation by real-time PCR assay based on the same target gene: three copies/microl for linearized plasmids, 26 copies/microl for VERO cell culture isolates, 14 copies/microl for full blood samples and 41 copies/microl for clinical buffy coats. Based on a limited sample number, the LAMP assay is comparable in sensitivity with conventional nested PCR (56kDa gene), with limits of detection well below the range of known admission bacterial loads of patients with scrub typhus. This inexpensive method requires no sophisticated equipment or sample preparation, and may prove useful as a diagnostic assay in financially poor settings; however, it requires further prospective validation in the field setting.